Displacement-based seismic assessment of masonry buildings for global and local failure mechanisms. Issue 1 (1st January 2017) - Ahmad, Naveed; Ali, Qaisar
Abstract: Seismic fragility functions provide an easy mean to estimate the vulnerability of structures, develop damage scenarios and quantify number of structures with different damage states for a given seismic hazard. This paper presents the derivation of fragility functions for different types of masonry structures in Pakistan using a European standard methodology. It included structures with reinforced concrete floors and wooden/steel floors with truss roof. The first class of masonry structures is considered with the in-plane shear damage in masonry walls with abrupt collapse of structure at the ultimate deformation capacity of in-plane walls. Masonry structures of second class are considered with the collapse of out-of-plane façade walls in case of the absence of ring beams and ties and presence of weak wall-to-wall and wall-to-floor connections. Monte Carlo simulation is used to generate random structures with different geometrical and mechanical properties, which are analyzed using fully probabilistic approach in order to assess their seismic vulnerability. The number of structures exceeding different damage states are quantified to compute the limit state exceedance probability correlated with the seismic intensity measure, mainly inelastic spectral displacement, peak ground acceleration and spectral acceleration at 0.30 s, to derive family of analytical fragility functions. The derived fragility functions are tested and validated against the recent 2005 Kashmir earthquake, which shows reasonable prediction performance. The derived fragility functions can be used to derive damage probability matrices and estimate socio-economic losses in the region for public awareness and community earthquake preparedness planning in order to mitigate future earthquake regional risk.